Agronomic performance of new peanut strains in the Cerrado - Heuert, Jair (2020)
This work aimed to evaluate the agronomic performance of new peanut strains in the Cerrado. The experiment was conducted at Embrapa Arroz e Feijão, located in Santo Antônio de Goiás-GO, in the 2019/20 harvest. A randomized block design was used, with four replications and fourteen treatments, ten lines: 17-1253 OL, 18-1973 OL, 18-2010 OL, 18-2055 OL, 18-2087 OL, 18-2101 OL, 18-2133 OL, 18-2136 OL, 18-2177 OL, 18-2182 OL and four commercial cultivars: BRS 421 OL, BRS 423 OL, BRS 425 OL and Granoleico. The plots were formed by two lines of three meters in length and spacing between lines of ninety centimeters. Severity of black spot, mass of 100 grains and pod yield were evaluated. The lowest severity of black spot was obtained in the genotypes BRS 421 OL, BRS 425 OL and 18-2133 OL. The most productive genotypes were BRS 423 OL, BRS 421 OL, 18-2133 OL, 18-2010 OL, BRS 425 OL and 17-1253 OL.